Acta radiologica
" ... publication of original research articles on diagnostic and interventional radiology, clinical radiology, experimental investigations in animals, and all other research related to imaging procedures ... provides complete updates on all radiological specialities and technical utilities, as well as physiology and physics related to imaging, including ultrasonography, computed tomography, radionuclide and magnetic resonance imaging."